1989
DOI: 10.1007/bf01974299
|View full text |Cite
|
Sign up to set email alerts
|

Nine years of practical experience with phenylamide resistance in Phytophthora infestans in the Netherlands

Abstract: Resistance to phenylamide fungicides in the Phytophthora infestans population in the Netherlands decreased from a level of 77~ of the samples containing resistant strains in 1980 to 0% in 1986 with decreasing use of metalaxyl, the only phenylamide fungicide registered for use against late blight in this country. Use of metalaxyl decreased because the fungicide alone and combinations of metalaxyl with preventive late blight fungicides were not commercially available from 1981 through the first part of the potat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Thus, Ph. infestans could evolve only asexually during the 150 years since its introduction into Europe (Goodwin et al ., 1994) but still managed rapidly to evolve virulence against new resistance genes introduced into potato and tomato, and evolved resistance to fungicides (Davidse et al ., 1989). In 1984, the A2 mating type as well as more A1 mating type genotypes of Ph.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Ph. infestans could evolve only asexually during the 150 years since its introduction into Europe (Goodwin et al ., 1994) but still managed rapidly to evolve virulence against new resistance genes introduced into potato and tomato, and evolved resistance to fungicides (Davidse et al ., 1989). In 1984, the A2 mating type as well as more A1 mating type genotypes of Ph.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance strategy for phenylamide fungicides adopted in the UK and Northern Ireland has been described by Urech & Staub (1985). In Holland, a different strategy has been adopted where the protectant materials are used early in the season, and the use of phenylamides is restricted to a maximum of two sprays within two weeks during critical conditions (presence of disease in the locality, conducive weather conditions) (Davidse et al, 1989). In Holland and the UK (Table 6), phenylamide resistance was detected in 42% and 81% respectively of samples tested in 1988.…”
Section: Discussionmentioning
confidence: 99%
“…In the Republic of Ireland, a monitoring programme to determine the levels of metalaxyl resistance in the P. infestans population showed that there was a decrease from 75% of all isolates tested in 1981 to 6% in 1983 (Dowley & O'Sullivan, 1985). In the Netherlands, resistance to metalaxyl also subsequently declined from 100% resistant isolates to 0% in 1986 (Davidse et al, 1989). In the mid-1980s, metalaxyl was reintroduced into both countries as a proprietary mixture with other dithiocarbamate fungicides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, resistance to metalaxyl has been reported in many Phytophthora spp. Most notably, resistance was first reported in P. infestans on potato in the Netheriands (10). Additionally, metalaxyl-resistant isolates have been reported in P. cactorum (43), P. citricola, P. capsici (4), P. parasitica (14), and P. nicotianae (40), as well as in other oomycetes such as Peronospora tabacina, Bremia lactucae (29), and Pythium ultimum (39).…”
mentioning
confidence: 97%